Our New Neo-Kantianism - Schnadelbach, Herbert; Noras, Andrzej J. (Folia Philosophica, 2006)
Herbert Schnädelbach’s article Our New Neo-Kantianism explores the contemporary revival of Neo-Kantianism. He argues that both historical and “new” Neo-Kantianism share an original program of systematic philosophy in the spirit of Kant—positioned between quasi-Hegelian totalitarian claims and naturalistic tendencies, between a scientific orientation and its critique. In the first section, Schnädelbach outlines the historical background: from Lange and Helmholtz’s physiologism, through Cohen’s logical idealism, to the Baden-Marburg school, showing how early Neo-Kantianism lost its methodological drive and liberal orientation He then frames contemporary Neo-Kantianism in two perspectives: 1. Methodological – emphasizing that the essence of the new Neo-Kantianism is a form of discourse (the “transcendental turn”), rather than adherence to Kant’s or Hegel’s historical concepts; central is the inquiry into the conditions of possibility and understandability of validity claims (Geltungsfragen). 2.Thematic – highlighting its ethical-political dimension: Neo-Kantianism rejects the utopia of reconciliation in favor of a perspective of finitude, combining an innate liberalism with reflection on freedom and fallibility of practical reason. In conclusion, Schnädelbach contends that new Neo-Kantianism is a historical fact of our present age—both a challenge and an inspiration to continue asking, “in Kant’s spirit,” about the limits of reason and the possibilities of philosophy amid the linguistic turn and hermeneutic pluralism.